2020
DOI: 10.3390/ijms21186487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IGF-1 on Proliferation, Angiogenesis, Tumor Stem Cell Populations and Activation of AKT and Hedgehog Pathways in Oral Squamous Cell Carcinoma

Abstract: (1) Background: Activation of the PI3K-AKT pathway controls most hallmarks of cancer, and the hedgehog (HH) pathway has been associated with oral squamous cell carcinoma (OSCC) development and progression. We hypothesized that fibroblast-derived insulin-like growth factor-1 (IGF-1) acts in oral squamous cell carcinoma (OSCC) cells, leading to the non-canonical activation of the HH pathway, maintaining AKT activity and promoting tumor aggressiveness. (2) Methods: Primary fibroblasts (MF1) were genetically engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…It is therefore likely that such connections exist between hsa-let-7c and IGF1R/PI3K/Akt. The PI3K/Akt signaling pathways are common to PE and play key roles in many cellular processes [ 26 ], such as invasion of trophoblast [ 27 ], angiogenesis [ 28 ], and pro-inflammation [ 29 ]. Park JK demonstrated that inhibition of the PI3K-Akt pathway may decrease sFlt1 secretion in human placental hypoxia models, which provides a useful therapeutic approach for PE [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that such connections exist between hsa-let-7c and IGF1R/PI3K/Akt. The PI3K/Akt signaling pathways are common to PE and play key roles in many cellular processes [ 26 ], such as invasion of trophoblast [ 27 ], angiogenesis [ 28 ], and pro-inflammation [ 29 ]. Park JK demonstrated that inhibition of the PI3K-Akt pathway may decrease sFlt1 secretion in human placental hypoxia models, which provides a useful therapeutic approach for PE [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts have also shown to be a source of IGF-1 (insulin growth factor 1) in OSCC, which promotes tumour cell proliferation through activation of PI3K-AKT and Hedgehog signalling pathways [ 59 ]. The matrix-remodelling capabilities of CAF may also affect tumour proliferation [ 60 ]; CAF-secreted collagens, collagen8A1 and collagen11A1 [ 61 ], have been shown to modulate tumour cell growth through interaction with DDR1 (Discoidin domain receptor 1), which is overexpressed in HNSCC tissues.…”
Section: Caf and Tumour Proliferationmentioning
confidence: 99%
“…Recent studies identified novel non-canonical regulation of GLI in various cancers. Especially, nuclear myocardin-related transcription factor in basal cell carcinoma [ 57 ], deregulated GSK3β in colon cancer cells [ 58 ], Ras–Raf–MEK ERK pathway in hepatocellular carcinoma [ 59 ], fibroblast-derived insulin-like growth factor-1 in oral squamous cell carcinoma [ 60 ], MAPK/ERK signaling in lung adenocarcinoma [ 61 ], transcriptionally-active androgen receptors in pancreatic cancer [ 62 ] and SOX2-BRD4 transcriptional complex in melanoma [ 63 ]. Additionally, studies in breast cancer models, EMT cells induce increased metastasis of weakly metastatic, non-EMT tumor cells in a paracrine manner, in part by non-cell autonomous activation of the GLI transcription factor.…”
Section: Discussionmentioning
confidence: 99%